Sosialisasi Ilmu Budidaya Ikan Lele dalam Ember di Pekarangan Rumah Warga Gp. Beurawe, Kota Banda Aceh - Hayati, Rahmah; Rahmiati, Rahmiati; Rosa, Elvrida; Fitri, Sri (Nawadeepa: Jurnal Pengabdian Masyarakat, 2023)
The resident was increased never be separated from the need for housing in the city. The land use was obtaining to make a house so that agricultural activities a difficult to carry out. These detentions were also experienced in the general public, especially in this service, the Gp. Beurawe society. This study aims to provide socialization to Gp. Beurawe society in Banda Aceh city for a catfish farming system in buckets using the aquaponics method. This system does not need to required land area, to a cheap, and easily system to everyone. This scheme was expected to be a solution to the problem of limited land, because the community around the service location has a condition of close to each other. Therefore, this community service activity needed to provide the better solution. This society activity apart from cultivating fish in buckets were a solution added for growing vegetables such as lettuce and mustard greens hydroponics system. The service method was carried out to provide education to the community at the Keuchik Office with assistance from a series of effective methods of distribution a bucket as well as hydroponic materials. The benefit of this services was obtaining knowledge for the people in Beurawe, especially around the City, regarding the application of the ''Budikdamber aquaponics'' system, namely fish farming in buckets in front of each house